Estimation of some salivary variables and oral health status of patients with chronic myeloid leukemia aged 45-55 years - Al-Shaikh Radhi, Nagham H; Al-Waheb, Athraa M (Journal of Baghdad College of Dentistry, 2013)
Background: Chronic myeloid leukemia is a cancer of the white blood cells characterized by the increased and unregulated growth of predominantly myeloid cells in the bone marrow. This study aimed to determine the effect of chronic myeloid leukemia on Dental caries and Oral health status including Gingivitis, Loss of attachment, Plaque index and Calculus index as well as evaluation of salivary flow rate and salivary interleukins-6 and tumor necrosis factor-?. Material and methods: Study group consisted of (75) subjects, (25) were newly diagnosed with chronic myeloid leukemia, (25) were taking medications (Glevic), and (25) were control subjects, all aged 45-55 years old. Collection of stimulated salivary samples was performed under standard conditions, then salivary flow rate and salivary cytokines estimation was done. Clinical examination and oral health assessment were carried out under the standardized conditions of oral health surveys of World Health organization. dental plaque was scored according to the criteria of plaque Index by Silness and Loe(1964), Dental calculus was scored following the criteria of calculus component of the periodontal Index (Ramfjord, 1959), assessment of gingival health done according to the criteria of gingival Index for Loe and Silness (1963) and loss of attachment done following the criteria of WHO (1997). Caries assessment was done according to the WHO modified Decayed-Missing-Filled Index (DMF) and examination was done with a plane mouth mirror and CPI probe.Results: DMFS index were higher in the newly diagnosed group followed by the control group and then the treated group but the LSD test showed that differences were statistically not significant between each two groups, Plaque index was higher in the newly diagnosed group, and the differences were statistically significant only between the newly and the control group (p